PENGARUH KONSENTRASI DAN JENIS ZAT PENGATUR TUMBUH TERHADAP PERTUMBUHAN STEK PUCUK JERUK NIPIS (Citrus aurantifolia) - Arifa Isti Suwardi; Pramono Hadi; Srie Juli Rachmawatie (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2023)
The purpose of this research is to ascertain how growth regulator concentration and type affect lime shoot cuttings (Citrus aurantifolia) growth. From November 2022 to February 2023, this study was carried out in Dusun III Pandanan Dukuh Biru RT 03/RW 01, Wonosari District, Klaten Regency, Central Java. At an elevation of about 118 meters above sea level, the research site is located. This study employed a CRD (completely randomized design) with two factors, namely three ZPT types at (Z1: extract of onions, Z2: coconut water, and Z3: IBA Chemical Hormones) and growth regulator concentrations (K1: 25%, K2: 50% , K3 : 75%). There were 108 experimental units totaling 36 with four replications and three sample plants each. The percentage of living cuttings, the age at which shoots appeared, the height of shoots, the number of leaves, the number of shoots, and root length were the parameters that were observed. used the One-Way ANOVA test of variance (Test F) at the levels of 5% and 1% to analyze the data. at a level of 5%, continued the Duncan Multiple Range Test (DMRT) examination. According to the findings of the research, the treatment of various types of PGR significantly affects the age of shoot emergence, plant height, and number of leaves. ZPT concentration had a significant impact on plant height and root length, but there was no significant interaction between the two in any of the observed parameters.